Exploring Research Trends in Entrepreneurship Studies: A Systematic Review through Bibliometric Analysis - Takayuki SAKAI; Tatsuhiko INOUE (AAOS Transactions)
This study employs bibliometric analysis to examine the consistency and fragmentation of research trends in entrepreneurship studies from 2000 to 2024. The findings reveal that four core themes-‘innovation,’ ‘entrepreneurship,’ ‘institutional theory,’ and ‘entrepreneurial orientation’-have been consistently central throughout the period. However, recent years have witnessed an increase in studies addressing emerging phenomena, such as crowdfunding and digital technologies, suggesting a trend toward thematic diversification. By tracing the chronological evolution of the knowledge base in entrepreneurship research, this study highlights the enduring theoretical foundations and underscores the need for more detailed investigations into emerging trends.